The British Orthopaedic Surgery Surveillance study: Perthes' disease: the epidemiology and two-year outcomes from a prospective cohort in Great Britain. (1st April 2022) - Perry, Daniel C.; Arch, Barbara; Appelbe, Duncan; Francis, Priya; Craven, Joanna; Monsell, Fergal P.; Williamson, Paula; Knight, Marian; ,
Abstract : Aims: The aim of this study was to evaluate the epidemiology and treatment of Perthes' disease of the hip. Methods: This was an anonymized comprehensive cohort study of Perthes' disease, with a nested consented cohort. A total of 143 of 144 hospitals treating children's hip disease in the UK participated over an 18-month period. Cases were cross-checked using a secondary independent reporting network of trainee surgeons to minimize those missing. Clinician-reported outcomes were collected until two years. Patient-reported outcome measures (PROMs) were collected for a subset of participants. Results: Overall, 371 children (396 hips) were newly affected by Perthes' disease arising from 63 hospitals, with a median of two patients (interquartile range 1.0 to 5.5) per hospital. The annual incidence was 2.48 patients (95% confidence interval (CI) 2.20 to 2.76) per 100, 000 zero- to 14-year-olds. Of these, 117 hips (36.4%) were treated surgically. There was considerable variation in the treatment strategy, and an optimized decision tree identified joint stiffness and age above eight years as the key determinants for containment surgery. A total of 348 hips (88.5%) had outcomes to two years, of which 227 were in the late reossification stage for which a hip shape outcome (Stulberg grade) was assigned. The independent predictors of a poorer radiological outcome were female sex (odds ratio (OR) 2.27 (95% CI 1.19 to 4.35)), age above six years (OR 2.62 (95% CI (1.30 to 5.28)), and over 50% radiological collapse at inclusion (OR 2.19 (95% CI 0.99 to 4.83)). Surgery had no effect on radiological outcomes (OR 1.03 (95% CI 0.55 to 1.96)). PROMs indicated the marked effect of the disease on the child, which persisted at two years. Conclusion: Despite the frequency of containment surgery, we found no evidence of improved outcomes. There appears to be a sufficient case volume and community equipoise among surgeons to embark on a randomized clinical trial to definitively investigate the effectiveness of containment surgery. Cite this article: Bone Joint J 2022;104-B(4):510–518.